Student Adaptation, Loneliness and Mental Health Profiles during the Second Wave of the Pandemic COVID-19 - Aikaterini Lampropoulou; Niki Georgakakou-Koutsonikou; Chryse Hatzichristou; Petros Roussos (MDPI AG, 2023)
Since the COVID-19 pandemic, adolescent mental health difficulties have increased. To understand adolescent adjustment, it is important to explore both mental health difficulties and indicators of resilience and well-being. The primary aim of this study was to explore the associations among resilience, subjective well-being (SWB), fear of COVID-19, and loneliness among adolescents during the second wave of the pandemic. Additionally, the study aimed to identify student profiles based on these variables. The sample consisted of 469 high school students (61% girls, 29% junior high school). Resilience was positively correlated with SWB and negatively with fear of COVID-19 and loneliness. Three student profiles were identified. The Resilient and Satisfied group (38%) consisted of students with the most positive adaptation, and the Average group (41%) involved students with middle scores in all variables, while the Vulnerable and Distressed group (21%) included those who struggled the most. The need for a tiered approach in providing school-based mental health support is discussed.